2020
DOI: 10.1093/icvts/ivaa192
|View full text |Cite
|
Sign up to set email alerts
|

Heat production during pulmonary artery sealing with energy vessel-sealing devices in a swine model

Abstract: OBJECTIVES Energy vessel-sealing devices are being increasingly utilized to seal pulmonary artery (PA) branches during lobectomy. Heat from these devices can potentially injure surrounding tissues. We evaluated heat production from devices in a live animal model. METHODS PA branches were sealed in pigs with 4 energy vessel-sealing devices: 2 ultrasonic (US), 1 advanced bipolar or 1 mixed US and bipolar (mixed) device. Thermoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In human ex-vivo PA sealing model, the mean bursting pressure of ultrasonic devices was twice as high as bipolar devices (Harmonic 416 mmHg, LiGasure 215 mmHg, EnSeal 134 mmHg) (12). In animal model, the mean tissue temperatures during PA sealing is about the same in ultrasonic and bipolar devices (70-78 ℃) but the instrument blade temperature is much higher in ultrasonic devices (224 vs. 83 ℃) (18). In histological and immunohistochemical analysis of pulmonary vessels divided by LigaSure, it was found that LigaSure sealing result in sealing of the adventitia only, without complete fusion of the layers of the PA walls.…”
Section: Energy Sealing Devices In Anatomical Lung Resectionmentioning
confidence: 97%
See 1 more Smart Citation
“…In human ex-vivo PA sealing model, the mean bursting pressure of ultrasonic devices was twice as high as bipolar devices (Harmonic 416 mmHg, LiGasure 215 mmHg, EnSeal 134 mmHg) (12). In animal model, the mean tissue temperatures during PA sealing is about the same in ultrasonic and bipolar devices (70-78 ℃) but the instrument blade temperature is much higher in ultrasonic devices (224 vs. 83 ℃) (18). In histological and immunohistochemical analysis of pulmonary vessels divided by LigaSure, it was found that LigaSure sealing result in sealing of the adventitia only, without complete fusion of the layers of the PA walls.…”
Section: Energy Sealing Devices In Anatomical Lung Resectionmentioning
confidence: 97%
“…To prevent premature division of the artery, it is very important to avoid tension or torsion for the entire activation. At the end of sealing, the instrument tip can reach temperatures exceeding 200 ℃ (18). To avoid a thermal injury for adjacent vessels, airway and parenchyma, it is critically important to maintain a short distance away from the surrounding tissue during activation, and to cool the instrument on the lung to be removed before using it for subsequent dissection.…”
Section: Surgical Technique For Pulmonary Vessel Sealing Using Energy Devicesmentioning
confidence: 99%